2009
DOI: 10.1074/jbc.m109.024026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Associated with HIV-1 Resistance to Acyclovir by the V75I Mutation in Reverse Transcriptase

Abstract: It has recently been demonstrated that the anti-herpetic drug acyclovir (ACV) also displays antiviral activity against the human immunodeficiency virus type 1 (HIV-1). The triphosphate form of ACV is accepted by HIV-1 reverse transcriptase (RT), and subsequent incorporation leads to classical chain termination. Like all approved nucleoside analogue RT inhibitors (NRTIs), the selective pressure of ACV is associated with the emergence of resistance. The V75I mutation in HIV-1 RT appears to be dominant in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
1
16
1
1
Order By: Relevance
“…Pre-steady-state kinetics. Assays were performed as described previously (9,14,31). 5Ј-labeled 20Dϩ3 primer (100 nM) was heat annealed with 200 nM 42D template.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-steady-state kinetics. Assays were performed as described previously (9,14,31). 5Ј-labeled 20Dϩ3 primer (100 nM) was heat annealed with 200 nM 42D template.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, V75I has been recently identified as a major acyclovir resistance mutation in cells co-infected with HIV-1 and herpes simplex virus (24,25). Structural analysis of HIV-1 RT showed that Val 75 plays a role in positioning the template nucleotide ϩ1, during the formation of the ternary complex (26).…”
Section: * This Work Was Supported By Spanish Ministry Of Science Andmentioning
confidence: 99%
“…impact on ATP-dependent phosphorolytic activity on primers blocked with several chain-terminating inhibitors. However, it should be noted that V75I impairs the incorporation of acyclovir-TP (25), and therefore, acyclovir excision is not expected to be relevant in vivo.…”
Section: Effects Of Substituting Val 75 In Wild-type Hiv-1 Rts On Thementioning
confidence: 99%
“…Biochemical studies showed that mutant V75I RT did not alter binding efficiency of ACV-triphosphate but increased incorporation of dGTP versus ACV-5Ј-triphosphate through a discrimination mechanism (28). This suggests that a discrimination mechanism may also be respon- sible for the observed HIV-1 resistance to 3Ј-azido-ddC.…”
Section: Discussionmentioning
confidence: 86%
“…The V75I mutation identified in the 3Ј-azido-ddC-resistant HIV-1 has also been observed in selection experiments with acyclovir (ACV) and a monophosphorylated prodrug of ACV (9,28). Biochemical studies showed that mutant V75I RT did not alter binding efficiency of ACV-triphosphate but increased incorporation of dGTP versus ACV-5Ј-triphosphate through a discrimination mechanism (28).…”
Section: Discussionmentioning
confidence: 96%